Cyclooctatetraenyl calcium and strontium amido complexes. Issue 36 (26th June 2018) - Sroor, Farid M.; Vendier, Laure; Etienne, Michel
Abstract : The first examples of Ca and Sr amido complexes built on a cyclooctatetraenyl platform are reported. Abstract : This paper reports the synthesis and structural characterisation of a series of cyclooctatetraenyl (C8 H8 ) complexes of calcium and strontium, most of them containing the bis(trimethylsilyl)amido ligand. Mixing MI2 (M = Ca, Sr), KN(SiMe3 )2 and K2 (C8 H8 ) in thf in a 2 : 2 : 1 ratio gave the inverse sandwich amido complexes [[(Me3 Si)2 NM(thf) x ]2 (μ-C8 H8 )] (M = Ca, x = 1; M = Sr, x = 2) (1-Ca, 1-Sr ) in fair to good yields. From a 1 : 1 : 1 ratio, the mixed potassium calcium complex [[(Me3 Si)2 NCa(thf)](μ-C8 H8 )K] (2 ) was obtained in good yield. The reaction of2 with a 1 : 1 mixture of CaI2 and KN(SiMe3 )2 yielded1-Ca confirming that the reaction could be carried out stepwise. Attempts at making heterobimetallic calcium strontium amido complexes from the reaction of2 with SrN(SiMe3 )2 2 led to redistribution reactions which afforded the potassium strontium complex [[K(Me3 Si)2 N2 Sr]2 (μ-C8 H8 )] (3 ) among other species. Complex3 was more conveniently synthesised in fair yield starting from a 2 : 4 : 1 molar mixture of SrI2, KN(SiMe3 )2 and K2 (C8 H8 ), respectively. Treatment of2 with PhC}CH in benzene yielded an insoluble complex tentatively formulated as the polymeric complex [CaK(CCPh)(C8 H8 )(thf) x ] n (4 ). Upon dissolution in thf, 4 underwent a redistribution reaction yielding the X-ray characterised [Ca(μ-C8 H8 )2 K2 (thf)2 ] (5 ) and a homoleptic calcium alkynyl complex [Ca(CCPh)2 (thf) x ]. Several compounds were characterised by X-ray diffraction as discrete or polymeric structures where Ca⋯Cπ interactions were identified in some cases. Despite identified drawbacks, such as the lability of the coordinated thf ligands and facile redistribution reactions, this study represents the first synthetic approach to cyclooctatetraenyl heavy alkaline-earth metal amido complexes.